NURSERY TECHNIQUES WITH JUVENILE CORAL TROUT, Plectropomus leopardus WITH DIFFERENT TYPES OF FOOD - Anak Agung Alit; Ketut Maha Setiawati; Tony Setia Dharma (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2014)
ABSTRACT Feed management is a critical factor in the nursery activities because food serves as an energy for growth and survival rates. The study aimed to determine the best feeding to improve growth and survival rates. Cultured of coral trout grouper seeds were used for this research in 9 fiber tubs each of  0.8 tonnes of sea water volume with 3 treatments and 3 replicates. The feeding treatments were (a) commercial feeding pelle; (b) trash fish; and (c) feeding combinations (50% pellets and 50% trash fish). The initial length of coral trout grouper seeds were 3 cm long. The pellet used was a commercial pellet with dose of 5-10% biomass, while the trash fish was clupeid fish. Feeding times were twice a daya at 08:00 and 16:00 local time. A complete random design was used as an experiment design. Data was analysed using ANOVA and descriptive statistics. Water qualities during larva rearing included water temperature, pH, salinity, DO, ammonia, nitrite, and phosphate. The results showed that growth dan survical rates was significantly affected by combination feeding method (50% pellet and 50% trash fish) with growth rate of 0.08% cm/day and survival rate of 60.20±2.34%. Keywords: Feed, trash fish, juvenile coral trout grouper, growth, and survival.